Development and evaluation of a phosphorus (P) module in RZWQM2 for phosphorus management in agricultural fields. (March 2019) - Sadhukhan, Debasis; Qi, Zhiming; Zhang, Tiequan; Tan, Chin S.; Ma, Liwang; Andales, Allan A.
Abstract: A few management tools can simultaneously describe dissolved and particulate P losses from agricultural fields. In this study a phosphorus (P) management tool was developed based on most recent scientific findings to meet this need, and it was subsequently incorporated into Root Zone Water Quality Model 2 (RZWQM2) to take advantage of its featured hydrologic and agricultural management subroutines. The RZWQM2-P model was evaluated against data collected in a tile-drained corn-soybean rotated field fertilized with inorganic P at South Woodslee, Ontario. The results indicate that overall the model satisfactorily simulated dissolved reactive P and particulate P losses through surface runoff and tile drainage with Nash-Sutcliffe model efficiency coefficient >0.65, percent bias within 25% and index of agreement >0.75. RZWQM2-P is a promising tool for P management, particularly for subsurface-drained fields. Further testing is needed to assess its performance under different fertilization (manure), soil, climate, and cropping conditions. Highlights: A phosphorus module was developed based on the most recent findings and incorporated into RZWQM2. Emphasis was given to simulate P loss particularly through tile drainage system. RZWQM2-P performed satisfactorily in simulation of P loss from agricultural field.